Textbook of obesity : biological, physiological and cultural influences - Akabas, Sharon R.; Lederman, Sally A.; Moore, Barbara J. , 1947- (John Wiley & Sons, 2012)
"Textbook of Obesity is a major new textbook, designed to cover all of the essential elements concerning obesity within nutrition, dietetics and health sciences courses. Providing core knowledge for students is an essential and urgent requirement to ensure that those graduating will be properly equipped to deal with the huge incidence of overweight and obesity, currently effecting almost two-thirds of the population of the USA and with incidences in much of the rest of the world rapidly catching up.Comprising 27 chapters, each carefully written in a user-friendly style by an expert in the area, this landmark publication provides a huge wealth of essential information for all those working in the subject area worldwide. Textbook of Obesity is organized into 5 parts. Part I helps the reader to understand the scope and complexity of the problem of obesity. Part II focuses on obesity etiology. Part III examines the health consequences of obesity for both children and adults. Part IV discusses the challenge of assessing obesity in humans and offers insights into community factors that influence the risk of obesity. Finally, Part V dedicates 13 chapters to a discussion of a wide variety of prevention and obesity treatment interventions that are currently in use.Textbook of Obesity is an essential purchase for students studying nutrition and dietetics, health sciences and related courses and the many health professionals dealing with obesity on a day-to-day basis. Essential and core information for students studying nutrition, dietetics and health sciences. Covers a topic of worlwide importance: an obesity epidemic is upon us. Suberb list of top class authors from across North America. Carefully peer reviewed and edited. An essential reference for all those working in the subject area"--Provided by publisher